1996
DOI: 10.1021/es960393v
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Trends and Historical Deposition of Polychlorinated Biphenyls in Canadian Midlatitude and Arctic Lake Sediments

Abstract: A study of PCB concentrations and fluxes in lake sediments was conducted to test the “global fractionation” hypothesis that deposition of semivolatile organics will decline while more volatile congeners will be enriched in polar regions. Sediment cores were collected from 11 remote lakes in Canada ranging from 49° N to 82° N and were dated using excess 210Pb and 137Cs. Sediment extracts were analyzed for up to 90 PCB congeners by capillary GC-ECD with confirmation by GC/high-resolution MS. Total PCB (∑PCB) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 39 publications
9
108
2
Order By: Relevance
“…The precision of the bathymetric map of Lake Hazen will be increased in the future by adding more spots, particularly along the shoreline and at the far ends of the lake. The volume of the lake based on our bathymetric interpolation is approximately 5.14 × 10 10 m 3 and the mean depth is 95 m; both figures are about 10% larger than previous estimates by Muir et al (1996) based on data in the Deane (1959) report.…”
Section: Lake Bathymetrycontrasting
confidence: 60%
See 2 more Smart Citations
“…The precision of the bathymetric map of Lake Hazen will be increased in the future by adding more spots, particularly along the shoreline and at the far ends of the lake. The volume of the lake based on our bathymetric interpolation is approximately 5.14 × 10 10 m 3 and the mean depth is 95 m; both figures are about 10% larger than previous estimates by Muir et al (1996) based on data in the Deane (1959) report.…”
Section: Lake Bathymetrycontrasting
confidence: 60%
“…Deane (1959:62), on the basis of 62 echo sounding traverses in 1958, suggested a maximum depth for the lake of 263 m and noted that the "main part of the lake shows a shallow, asymmetrical, U-shaped depression, with the deepest part about half-way between the centre of the lake and the north shore." Muir et al (1996), using the data from Deane's work, reported a maximum depth of 263 m, mean depth of 85 m, and approximate lake volume of 4.55 × 10 10 m 3 . Sediment coring in 1990 at a site northeast of Johns Island in the deep zone identified by Deane (1959) was conducted to a maximum depth of 254 m (G. Brunskill, Australian Institute of Marine Science, Townsville, Queensland, pers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, site 1 concentrations happen to be largely dominated by 8CBs. Evidence suggests that more highly chlorinated PCB congeners commonly accumulate near the source of PCBs (Ashley and Baker, 1999;de Mora et al, 2005;Hong et al, 2005), whereas less chlorinated PCB congeners may be transported over longer distances (Muir et al, 1996). This may be a possible explanation to the problem.…”
Section: Correlation Of Pcbs With Physicochemical Parametersmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCB) have been amongst the most heavily studied of pollutants in this regard and reports of PCB migration include those in Northern Hemisphere soils (Meijer, et al, 2002), European high mountain lakes (Carera et al, 2002) levels observed in Norwegian mosses (Lead et al, 1996), deposition patterns in Canadian lakes (Muir et al, 1996) and Russian Lakes (McConnell et al, 1996). Studies universally point to enhanced retention of the more chlorinated PCB congeners at lower latitudes, probably reflecting a more facile volatilization of the simpler PCBs and their subsequent migration to the poles.…”
Section: Northern Hemispherementioning
confidence: 99%